2020
DOI: 10.1177/2473974x20921141
|View full text |Cite
|
Sign up to set email alerts
|

Medical Malpractice Trends in Thyroidectomies among General Surgeons and Otolaryngologists

Abstract: Objectives This study aims to examine litigation trends with thyroidectomies in the United States from 1984 to 2018. Methods We used the Westlaw legal database to collect data on the defendant, plaintiff, case demographics, alleged reasons for malpractice, additional complications, and case outcomes. Results The most common reason for litigation was vocal cord paralysis (51%, n = 28), with the majority ruling in favor of the defendant (64%, P = .042). Of those, 43% of cases (n = 12) were due to unilateral recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Litigation trends associated with thyroid surgery in the USA indicate that the most common claim was for vocal fold paralysis and the need for tracheostomy, with issues surrounding informed consent accounting for 30 per cent of claims. 8 Adjusting our data to surgical complications, we show similar results, where the most common injury cited was nerve injury (n = 8), for which two claims (25 per cent) included cause codes for 'failure to warninformed consent'. Our data concur with the most recent review of 161 cases in thyroid surgery in England by Dent and Bagnall, 9 who presented nerve injury as the most common surgical complication.…”
Section: Discussionsupporting
confidence: 56%
“…Litigation trends associated with thyroid surgery in the USA indicate that the most common claim was for vocal fold paralysis and the need for tracheostomy, with issues surrounding informed consent accounting for 30 per cent of claims. 8 Adjusting our data to surgical complications, we show similar results, where the most common injury cited was nerve injury (n = 8), for which two claims (25 per cent) included cause codes for 'failure to warninformed consent'. Our data concur with the most recent review of 161 cases in thyroid surgery in England by Dent and Bagnall, 9 who presented nerve injury as the most common surgical complication.…”
Section: Discussionsupporting
confidence: 56%
“…An integration and concurrent analysis of findings from ultrasound and elastography, radioisotope scan and MRI is most likely going to increase the accuracy of predicting the likelihood of FTC. The extent of vascular or capsular invasion of the FTC into may also be determined without the need for an invasive biopsy or a costly and potentially risky diagnostic lobectomy [ 176 , 217 , 218 , 219 , 220 , 221 , 222 , 223 ] Radiomics enables segmentation of the tumor and facilitates a thorough analysis of the tumor and the TME [ 163 , 224 , 225 ].A thorough analysis of a thyroid nodule and the TME may enable a “virtual” biopsy of the lesion and accurate histological diagnosis and grading of the tumor, like what would be achieved following a tissue or liquid biopsy. Some of the imaging investigations, such as [ 18 F] FDG PET/CT and [ 18 F] FDG/MRI, can localize metastases from FTC when there is discordance between the serum Tg level and the results of a whole-body radioiodine scan (WBS) [ 72 , 131 , 142 , 226 ].…”
Section: Multi-omics Of Follicular Carcinoma and Other Thyroid Tumorsmentioning
confidence: 99%
“…Other problems that can be addressed if AI is implemented is the incorrect risk-stratification of patients who have FTC and the appropriate level of TSH suppression in intermediate and high-risk patients. Additional benefits of AI is accurate calculation of I-131 dose for ablation, adjuvant therapy or treatment, a delay in the detection of progression, recurrence, and de-differentiation of the tumor, and prediction of the response to treatment [ 183 , 221 , 223 , 231 , 234 ]. The use of AI in the management of FTC can simultaneously incorporate background personal, life-style, and environmental factors (digital personal twin), imaging results (radiomics), FNAC and histological results (pathomics), mutational analysis (genomics), histone modification and transcriptomics (epigenomics), and post-translational changes (proteomics and metabolomics).…”
Section: Artificial Intelligence and Management Of Ftcmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, many studies have now confirmed the long-term complications and consequences of thyroid surgery for patients and healthcare systems despite the use of modern technologies such as neuromonitoring. The rates of unilateral and bilateral recurrent nerve paralysis and the rate of permanent hypoparathyroidism remain stable and low at 1-2%, but this is responsible for significant morbidity from a patient perspective and is very costly on the scale of entire populations [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%